Enhanced mechanical property and flame resistance of graphene oxide nanocomposite paper modified with functionalized silica nanoparticles. (15th November 2019) - Yu, Zhi-Ran; Li, Shi-Neng; Zang, Jing; Zhang, Ming; Gong, Li-Xiu; Song, Pingan; Zhao, Li; Zhang, Guo-Dong; Tang, Long-Cheng
Abstract: Graphene oxide (GO) paper with outstanding integrated multiple functionalities (good mechanical performance, thermal stability and flame resistance, etc.) is strongly needed for numerous potential applications in cutting-edge fields. In this work, we report a facile and green process to fabricate GO-based nanocomposite papers via introducing functionalized silica (f-SiO2 ) nanoparticles. The results reveal that addition of f-SiO2 produces simultaneous improvements in mechanical strength, stiffness and flame resistance for GO paper. With incorporation of 10 wt% f-SiO2, the tensile strength, elastic modulus and toughness of the GO/f-SiO2 nanocomposite papers can be increased by about 51%, 317%, and 69%, respectively. Various characterizations disclose that hydrogen bonds and covalent interactions between GO sheets and f-SiO2 mainly contribute to the effective load transfer and energy dissipation between them, and thus leading to the improvements of mechanical properties. Based on the structural observation and analysis, the improved flame resistance of the GO/f-SiO2 papers should be attributed to the formation of rGO/SiO2 protective char, which are derived from the decomposition and redeposition of the grafted silane molecules and inorganic SiO2 and thermal reduction of GO into rGO. Our results suggest that the mechanical and thermal properties of GO papers can be tuned by introducing inorganic/organic f-SiO2, providing a new route for the rational designing and development of mechanically flexible and flame-retardant GO-based nanocomposite paper materials. Highlights: Graphene oxide/APTS modified silica nanocomposite papers were designed and synthesized. The obtained nanocomposite papers show simultaneous improved mechanical properties and flame resistance. The enhanced hydrogen bonds and covalent interactions between graphene oxide sheets and nanoparticles contribute to the improved mechanical properties. The formation of SiO2 protective layer derived from the decomposition of grafted silane molecules endows GO/f-SiO2 papers an attractive flame retardant property.